Higher Education Emergency Relief Funds (HEERF) (2022)
The Higher Education Emergency Relief Fund (HEERF) grant program provides financial aid to students and higher education institutions to help with new expenses and revenue losses associated with the COVID-19 pandemic. The program was created by Congress as part of the Coronavirus Aid, Relief, and Economic Security (CARES) Act in March 2020, and received additional funding from the Coronavirus Response and Relief Supplemental Appropriations Act (CRRSAA) in December 2020 and the American Rescue Plan Act (ARPA) in March 2021. HEERF has provided about $75 billion in aid to higher education students and institutions. California State University Channel Islands received over $50 million in HEERF aid.